Information Technology Epoch: Physical and Institutional Challenges to Female Gender in Civil Registration and Vital Statistics - Professor Dr. Mmoon Khan Khattak; Mr. Tehzeeb Ali; Dr. Zubaida Khatoon Khattak; Mr. Amin Khan Khattak (`, 2025)
Allah Almighty has blessed every human being with a distinctive personality that is known through one’s identity. In modern day world, such identities are universally digitized through information technology, through registering and recording, through nationwide connected data basis. In the Information Technology Epoch, speed is the defining metric, acting as the new scale for competitive advantage, enabling real-time data processing, innovation, and digital transformation. Due to this phenomenon, ideally, as per need of time, it is necessary that a person records and registers oneself at these authorized digital offices serving as registration centers. However, here at the study region, due to a number of factors, the ratio of female gender’s registration is lower creating identity issues for them. Therefore, the main objective of the study has been to analyze the physical, and institutional challenges with respect to female gender, in relation with civil registration and vital statistics in District Orakzai. The study adopted a quantitative research design relying on primary data collected through a structured questionnaire administered to respondents ranging their ages from 18 years to 49 years at village council offices. Primary data was analyzed using Likert scale (developed in 1932 by Rensis Likert) to identify respondents’ views and experiences. The findings revealed that the females’ registration was significantly influenced due to physical, and institutional factors in the study region. It is recommended that physical and institutional challenges to females in civil registration and vital statistics be mitigated for improving females’ registration participation. Key Words: Civil registration, gender, female(s), information technology, vital statistics, institutional challenges.